Equity in Enrolment and Completion in Elementary Schooling in India : Evidence from Recent Household Surveys - World Bank (Washington, DC, 2014)
This policy note analyses the evidence on the various equity issues relating to the participation and completion of elementary school education in India is based on the data collected by the national sample survey (NSS) and national family health surveys (NFHS), the latest year being looked at is 1998-99. this documentation of state-wise regional, community, gender and income inequities therefore do not take into account the progress made by states in reducing the inequities under the district primary education program (DPEP) program for the last 8 years. in fact, some of the issues which comes out of this study and needs attention is probably already addressed under some of the new programs already being undertaken by the MHRD, such as the sarva shiksha abhiyan (SSA). however, by filing these issues in a systematic manner, we hope to draw continued attention to the status of these issues in the programs.